Peningkatan Mutu Laboratorium dalam Aspek Keselamatan dan Kesehatan Kerja pada Laboratorium - Anggarsari, Desye Novita; Ni'mah, Anisa Luthfiyyatin; Malichatin, Hanik (Jurnal Laboratorium Khatulistiwa, 2022)
Â The laboratory is one of the academic facilities contained in an educational institution. The benefits of the laboratory being used in scientific activities and searching for valid data related to the type of practicum-based learning. In educational institutions there are several types of laboratories such as laboratories (IPA, Engineering, Computers), in the current era laboratories can develop rapidly towards science and technology. In the management of the laboratory premises there are provisions and recommendations that are applied. One of the applications in the laboratory is to provide safety & health directions. Health in the health laboratory related to each individual is related to the practicum, because health problems caused by chemicals result in disruption of productivity levels. Laboratory work safety is the use of personal protective equipment available in the laboratory to protect individuals from the dangers of practices carried out in the laboratory.